2010
DOI: 10.1248/bpb.33.1949
|View full text |Cite
|
Sign up to set email alerts
|

Intratracheal Sensitization/Challenge-Induced Biphasic Asthmatic Response and Airway Hyperresponsiveness in Guinea Pigs

Abstract: In most experimental model of asthma using guinea pigs, the animals are made to inhale an aerosolized antigen which passes through the nasal cavity. In the present study, we attempted to create an animal model of asthma showing a biphasic asthmatic response and airway hyperresponsiveness, in which the allergic responses are restricted to the lung. Guinea pigs were sensitized by the intratracheal instillation of ovalbumin (OVA)؉Al(OH) 3 once a day for 7 d, and then intratracheally challenged with OVA 12 d after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…We first successfully established the animal model of airway allergic inflammation. Consistent with previous reports, [33][34][35] our findings in vivo suggested that OVA challenge resulted in a significant increase of the OVAspecific Th2 subset, elevation of OVA-sIgE levels, and intensive eosinophil infiltration in the airway walls, which mimics the typical symptoms of human allergic airway inflammation. We then investigated the changes in basophil number and activity following OVA challenge.…”
Section: Discussionsupporting
confidence: 92%
“…We first successfully established the animal model of airway allergic inflammation. Consistent with previous reports, [33][34][35] our findings in vivo suggested that OVA challenge resulted in a significant increase of the OVAspecific Th2 subset, elevation of OVA-sIgE levels, and intensive eosinophil infiltration in the airway walls, which mimics the typical symptoms of human allergic airway inflammation. We then investigated the changes in basophil number and activity following OVA challenge.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have utilized single-or double-chambered plethysmographs to show allergen-induced responses in the guinea-pig [28][29][30][31]. In this study, we used the forced-oscillation technique to demonstrate a prominent increase in lung resistance during EAR [32].…”
Section: Discussionmentioning
confidence: 99%